Training on Utilizing Waste into Creative Artworks for Students of Madrasah Uthmaniah (ABIM) Malaysia - Cahyanto, Bagus; Bela Dina, Lia Nur Atiqoh; Kampun, Hdariyani Binti; Ulmy, Adella Yauma; Daroini, Hasanatud; Farahdilla, Ariska (Universitas Nurul Jadid, 2025)
Waste management is an issue that requires serious handling, one solution that can be done related to the waste problem in schools is through training in making creative artwork using waste or used goods. This community service activity was carried out at Madrasah Uthmaniah Malaysia with a training method that includes several stages such as (a) presentation of materials, (b) implementation of training, (c) practical assignments, and (d) monitoring and evaluation. This activity is also packaged in direct practice to provide practical experience to students, can contribute to learning arts and culture in schools, as well as awareness of the importance of sustainable environmental management. This activity ended with filling out a questionnaire and feedback by participants which showed that the majority of participants gave a positive response to the community service activities that had been carried out.